Iliac crest avulsion fracture and staged return to play: A case report in youth soccer - Materne, O.; Haddad Hani A.; Duncan, R. (Science and Medicine in Football, 2019)
Purposes: Iliac crest avulsion fracture is an unusual pathology. Final functional outcomes are generally excellent, though recurrent symptoms may delay the return to play. There is a lack of published evidence on conservative management and rehabilitation for this injury. The aim of this case study is to describe a comprehensive and successful rehabilitation plan of a youth elite soccer player. Case Presentation: A 16-year-old male centre-back soccer player sustained a left iliac crest avulsion fracture. The injury occurred while executing a right-footed long cross of the ball, right to left. Intervention: After a short period of rest (including a lumbosacral orthosis), rehabilitation progressed from non-weight-bearing through to an array of sports-specific full weight-bearing exercises. The field sessions were individualised, based on the player`s physiological profile and match characteristics in non-linear dynamics. Outcomes: The player recovered fully and returned pain-free at the same international football level after 14 weeks. There has been no recurrence since. Conclusion: An iliac crest avulsion fracture in youth soccer can be fully recovered by conservative management. Early diagnosis, close monitoring, progressive (individualised) sports-specific rehabilitation and good compliance were key factors in the successful return to play.